Lower Calciferol Level In Diabetic People And Their Association With Glycated Haemoglobin - Kalsoom, Rizwana; Khan, Muhammad Rehan; Umer, Saima; Ustrana, Shahjahan; Ahmed, Irshad; Kalsoom, Farhana (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To investigate the relationship between low calciferol levels and glycated hemoglobin in diabetics with normal blood sugar control. Methods Vitamin D (calciferol) levels and HbA1c levels were examined in 110 individuals with type 2 diabetes and a control group, ensuring both groups were similar in terms of gender and age. Calciferol (25(OH)D3) level was determined using the method of radioimmunoassay (RIA) and the High-performance liquid chromatography technique (HPLC) was used to determine the glycosylated hemoglobin (HbA1c) level. Results Calciferol levels were found low in the test group (type 2 diabetic patients) 18.16 ± 0.85 ng/ml as compared to the control group 24.38 ±2.01ng/ml with (p≤0.000). The calciferol levels were assessed and it was found that they were inversely related to glycated hemoglobin levels in the test group (r (2) = 0.047, linear regression, p ≤ 0.009,). Calciferol levels were also inversely associated with glycated hemoglobin levels in combined analyzed data of test and control groups (p ≤ 0.001, r (2) = 0.079). Conclusion The study determined that the calciferol levels were found with decreased frequency in the diabetic group as compared to the control group and it showed that vitamin D levels have a key role in glycemic control in type 2 diabetic patients. These findings support the idea that type 2 diabetic patients may improve their glycemic control by using vitamin D supplementation.